ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAKAN PENGGELAPAN PAJAK PADA WAJIB PAJAK ORANG PRIBADI (Studi Empiris pada Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Kabupaten Demak) - Bahtera Afrikani Sri Wuri Handayani; Dul Mu'id (Diponegoro Journal of Accounting, 2019)
This study is concerned with the occurrence of tax evasion by tax actors who then direct this study to develop an empirical model of tax evasion measures described by the variables of tax understanding, perception of justice, taxation system as independent variables, taxpayer compliance as the mediating and religiousity variables taxpayer as a moderating variable.Data related variables studied were obtained through interviews to taxpayers of individuals who pay taxes late or not pay taxes in the Tax Office (KPP) Pratama Demak by using questionnaires. The data obtained then analyzed using Multiple Regression analysis approach.Empirical testing conducted in this study yielded five conclusions, namely the understanding of taxation is a variable that can significantly explain the occurrence of changes in taxpayer compliance, perception of justice is a variable that can significantly explain the occurrence of changes in taxpayer compliance, taxation system is a variable that real is able to explain the occurrence of changes in taxpayer compliance, taxpayer compliance is a variable that can explicitly explain the occurrence of tax evasion by taxpayers, and taxpayer religiosity is not proven to moderate the influence of taxpayer compliance with tax evasion.